[FORA N]: ESTUDO DE UMA CONSTRUÇÃO À LUZ DA LINGUÍSTICA FUNCIONALISTA - Silva, Ana Carolina Luz da (2022)
Studying the language in its communicative multifacets and understanding its many uses are parts of the process of acquiring information about the culture and history of a community. This dissertation is characterized as a linguistic study that aims to investigate the structure [Fora N] from the perspective of Functional Linguistics, more specifically from the Use-Based Models, by Goldberg (2006), Bybee (2016) and Traugott and Trousdale (2021), and from cognitive-functional linguistics. It is from these assumptions that this work understands [Fora N] as a construction, which is a “conventional symbolic unit”, according to Croft (2005). With a qualitative-quantitative, descriptive and documentary methodology, according to Gil (2002), the collection of the corpus for the phenomenon analysis was made Corpus Now, one of the corpora available in the database “O Corpus do Português”. This database provides samples from the years 2012 to 2019/1, all of which were used for research and samples containing [Fora N]. The corpus of this research, totalizing 604 samples, was analyzed according to formal and functional parameters from Croft (2001) and, through the analyses, it was possible to verify that the structure [Fora N] is characterized as a construction that emerged from a specific discursive-pragmatic context, revealing, in the occurrences, a construction with high frequency of use.